2020
DOI: 10.1111/bjhp.12430
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19‐related anxiety predicts somatic symptoms in the UK population

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
145
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(187 citation statements)
references
References 13 publications
21
145
1
6
Order By: Relevance
“…Consistent with past studies [ 6 , 26 ], age was found to be a predictor of mental health problems for the general population in Malaysia. This is also consistent with studies of healthcare workers, where older healthcare workers were less likely to have mental health problems [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with past studies [ 6 , 26 ], age was found to be a predictor of mental health problems for the general population in Malaysia. This is also consistent with studies of healthcare workers, where older healthcare workers were less likely to have mental health problems [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…Distress, anxiety, depression, and insomnia are relevant mental health disorders due to their prevalence during severe acute respiratory syndrome (SARS) and COVID-19 outbreaks [ 2 , 3 , 4 , 5 ]. A number of studies have predicted mental health by means of demographic variables [ 2 , 3 , 6 ], but little research has predicted mental health during the COVID-19 pandemic based on adults’ health-related variables. This study aims to examine individuals’ perception of health conditions and of test availability as predictors of insomnia, anxiety, depression, and distress during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…As such, COVID-19 can lead to the emergence of various sorts of psychosocial distress ( Lima et al, 2020 ; Torales, O’Higgins, Castaldelli-Maia, & Ventriglio, 2020 ; Zheng, 2020 ), presumably reflecting the “second tsunami” of the COVID-19 pandemic ( Dutheil, Mondillon, & Navel, 2020 ). Indeed, emerging initial findings are documenting the psychosocial toll of the pandemic, reflected in elevated levels of fear ( Lee, Mathis, Jobe, & Pappalardo, 2020 ), stress ( Lai et al, 2020 ), general anxiety ( Hyland et al, 2020 ; Shevlin et al, 2020 ), as well as health-related and economic anxiety ( Bareket-Bojmel, Shahar, & Margalit, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…infection and cancer prognosis are recommended [13,15] which postpones routine follow-up in the absence of symptoms. However, high COVID-19-related anxiety is associated with reporting more somatic symptoms [33], and so women with high cancer-related anxiety due to missed screening may report more symptoms, leading to unnecessary healthcare contacts and exposure to COVID-19. Similarly, the recommendation to defer surgery in favour of hormone therapy (HT) [13][14] could have negative effects beyond cancer-related anxiety as a small proportion of this sample reported worsening HT side-effects and difficulty accessing medication which can adversely affect adherence [34][35].…”
Section: Discussionmentioning
confidence: 99%